1998
DOI: 10.1063/1.122696
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the concentration and temperature dependence of the fundamental energy gap in AlxIn1−xSb

Abstract: We use transmission spectroscopy to determine the energy gap for the AlxIn1−xSb alloy system in the Al concentration range from 0% to 25% from cryogenic to room temperature. The samples are epitaxial layers grown by molecular beam epitaxy on GaAs substrates. Our room temperature results are compared to those from two earlier studies. In our Al concentration range, we find a linear change of energy gap with alloy lattice constant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 4 publications
0
22
0
1
Order By: Relevance
“…The mobilities of the samples studied range from 70 000 cm 2 / Vs to 150 000 cm 2 / Vs. The energygap discontinuity 19 as well as the band offsets 20 are well characterized in this strained-layer system.…”
mentioning
confidence: 80%
“…The mobilities of the samples studied range from 70 000 cm 2 / Vs to 150 000 cm 2 / Vs. The energygap discontinuity 19 as well as the band offsets 20 are well characterized in this strained-layer system.…”
mentioning
confidence: 80%
“…Table 1 lists the parameters used in the SPM calculations for each QW width considered. For each well width, the doping density N d and spacer thickness S are varied providing sixteen different SPM solutions for a given W. Material parameters used in the SPM calculations were derived from transmission spectroscopy performed by Dai et al [37] to determine the bandgap energies of In 1-x Al x Sb. The InSb QW is assumed to be lattice matched to the lower barrier and strained accordingly (see Table. 1).…”
Section: Calculation Of Coupling Parametersmentioning
confidence: 99%
“…While absorption measurements of Agaev and Bekmedova [25] yielded a linear variation of the direct energy gap with composition and Dai et al [26] found a linear variation of the direct energy gap with alloy lattice constant (i.e., composition) for InSb-rich AlInSb, our result is in good agreement with that reported by Isomura et al [27] using electroreflectance determination, with the empirical curve charting the increase of the bowing parameter with lattice mismatch between the binary constituents [28] and with the recommended value of Vurgaftman et al [29] that was based on the fact that the electroreflectance measurements should have been more precise than the absorption experiments of Agaev and Bekmedova. Fig.…”
Section: Energy Gapsmentioning
confidence: 99%